2019
DOI: 10.3390/ijerph16203979
|View full text |Cite
|
Sign up to set email alerts
|

Water Footprint of Food Consumption by Chinese Residents

Abstract: Water shortages are a worldwide problem. Virtual water and the water footprint link water resources, human beings and agricultural products, and are effective tools to alleviate water-resources stress. The production of agricultural products consumes a large amount of water, and food is the most basic consumer good for human survival, so it is very necessary to study the water footprint of residents’ food consumption, which is also the weak point of current research on virtual water and the water footprint. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 61 publications
0
12
0
Order By: Relevance
“…Furthermore, a study using Swiss participants showed that perceived healthiness was especially determined by fat content, organic label, and processing [126]. Paquette [127] wisely observed that the perception of healthy eating was one of the many determinants of eating patterns.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a study using Swiss participants showed that perceived healthiness was especially determined by fat content, organic label, and processing [126]. Paquette [127] wisely observed that the perception of healthy eating was one of the many determinants of eating patterns.…”
Section: Resultsmentioning
confidence: 99%
“…In other words, perception of environment impact depends on packaging. Even if, according to food type, the real main environmental impact may be different, such as water consumption [127] or deforestation for beef meat production, packaging is for sure a very easy to use indicator for Environmental concern is gaining importance in consumer food choices, generating changes in production and supply and thus demonstrating how the consumer can contribute to environmental health.…”
Section: Capacity To Maintain Current Health State By Eating the Righmentioning
confidence: 99%
See 1 more Smart Citation
“…The water footprint (WF) is a useful indicator that can reveal the life-cycle water occupation in producing food [11]. An upward trend of water footprint of China's food consumption has been proved by Zhang et al [12]. Although population growth is a great contributor to this growing water footprint [13], the effect of diet transition should also be paid attention to.…”
Section: Introductionmentioning
confidence: 99%
“…As to food producers and consumers, every aspect of the food life cycle can strive to reduce the impact of food on the environment [ 14 ]. We can advocate a balanced diet structure, reduce food waste, and cut down those unnecessary energy intakes [ 15 , 16 , 17 ]. Today, the global population’s food intake accounts for 19–29% of the total greenhouse gas emissions, 70% of freshwater consumption, and 38% land use [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%